Liberalization and Electricity Policy Changes: Problems and Challenges in the Electricity Sector in Indonesia - Paryono, Paryono; Absori, Absori; Dimyati, Khudzaifah; Basri, Muinudinillah; Rismawati, Shinta Dewi (International Journal of Energy Economics and Policy, 2019)
This paper analyzes the impact of changes in electricity policy in Indonesia. The purpose of this paper is to provide an overview of the development of electricity sector regulations in Indonesia and their impact. Based on the study conducted, concluded: that the Indonesian government made a change in electricity policy under the influence of international donor agencies, International Monetary Fund (IMF) with a Letter of Intent (LOI) namely the liberalization of the electricity sector in Indonesia brought to the free market. In 2014 the Indonesian government plans to build power generation infrastructure reaching 35 thousand MW, and the percentage of infrastructure ownership is private (foreign) is more dominant, this is contrary to article 33 paragraph 2 of the 1945 Constitution of the Republic of Indonesia. The state of Indonesia with these changes is likely to be held captive by the interests of global capitalism by dictating electricity policy. Keywords: Liberalization, Electricity Policy, Capitalism, Indonesia JEL Classifications: G18, Q43, P12 DOI: https://doi.org/10.32479/ijeep.8636